Penanganan Pengaduan Masyarakat Dalam Pelayanan Publik Mengenai Izin Mendirikan Bangunan (IMB) Di Badan Pelayanan Perizinan Terpadu Kabupaten Badung - Diah Sanjiwani, Ni Putu; Dewi Pascarani, Ni Nyoman; Winaya, I Ketut (CITIZEN CHARTER, 2014)
ABSTRACT Service giving for the public is a major obligation of the government. However, the public still feel the performance and management of public service was being still un-optimal especially in the Integrated Licensing Service of Badung regency, so that public services generally become target of criticism and unsatisfaction of the public who was recieved the services which until certain limits put themselves as consumers of the public service. Viewed from the complaints submitted by public, this study aims to find out the form of the complaint management that Â submitted by the public in making of building permit (IMB) by the Integrated Licensing Service of Badung regency. This study is qualitative descriptive method. This study is qualitative descriptive method. To obtain the data, researcher was conducted observations the phenomenon at site directly and conduct in-depth interviews with sources associated with public complaints in the Integrated Licensing Service of Badung regency. Keywords: Public Service, Complaint Handling, Service Quality